Principles of Security and Trust - Focardi, Riccardo (Springer, 2015)
This book constitutes the refereed proceedings of the 4th International Conference on Principles of Security and Trust, POST 2015, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2015, in London, UK, in April 2015. The 17 regular papers presented in this volume were carefully reviewed and selected from 57 submissions. In addition, one invited talk is included. The papers have been organized in topical sections on information flow and security types, risk assessment and security policies, protocols, hardware and physical security and privacy and voting.